Students’ Needs of Arabic Speaking Material Using the Integrated Local Wisdom in the 21st-Century Skills Model - Mohamad Sarip (STAI Hubbulwathan Duri, 2022)
This study aimed to obtain the results of the analysis of the needs for speaking Arabic teaching materials through the basic values of local wisdom that are relevant to 21st-century skills. The research method used qualitative descriptive phenomena that occur in the field related to the need for teaching materials to speak Arabic. Participants were students and teachers of Arabic speaking courses. Data were collected through observation, documents and questionnaires. Technical analysis of data was carried out through the stages of data reduction, data presentation, and concluding. In addition, the data analysis technique used expert judgment. The findings show that teaching materials for speaking Arabic must be relevant to the cultural values of local wisdom and in harmony with the culture in Arabic so that students still have nationalist character values. So, teaching materials for speaking Arabic must present materials that can develop critical thinking patterns in the communication process, reflect the cultural values of the archipelago or local wisdom values that are in harmony with the culture in Arabic, and meet the demands of 21st-century skills so that students can compete in the era of globalization.